Efforts and Roles Of Parents as Mentors In Supporting the Fulfillment of Students’ Rights and Obligations in Elementary Schools - Salmi, Wan Fahrina (International Journal of Students Education, 2024)
Fulfillment of students’ rights and obligations in elementary schools is a shared responsibility between schools, students, and parents. Parents as mentors have an important role in supporting the formation of students’ character and academic abilities. This study aims to identify the efforts and roles of parents in supporting the fulfillment of rights, such as the right to education, protection, and participation, as well as obligations, such as learning discipline, respecting teachers, and obeying school regulations. In addition to being the first teacher, parents are also the closest friends to share feelings and complain about all problems related to school activities. Good communication carried out by parents and children will be important because it can strengthen the relationship between parents and children. This study uses a literature review method by collecting data from various sources, including journals, books, and relevant articles. The results of the study indicate that parental involvement, such as providing emotional support, monitoring learning activities, and communicating with teachers, is a major factor in student success. In addition, establishing a learning routine at home and providing positive role models are also strategic steps. By understanding this role, parents can help create a supportive learning environment for their children